Fish-derived antimicrobial peptides: Activity of a chionodracine mutant against bacterial models and human bacterial pathogens. (July 2019) - Buonocore, Francesco; Picchietti, Simona; Porcelli, Fernando; Della Pelle, Giulia; Olivieri, Cristina; Poerio, Elia; Bugli, Francesca; Menchinelli, Giulia; Sanguinetti, Maurizio; Bresciani, Alberto; Gennari, Nadia; Taddei, Anna Rita; et al.
Abstract: The increasing resistance to conventional antibiotics is an urgent problem that can be addressed by the discovery of new antimicrobial drugs such as antimicrobial peptides (AMPs). AMPs are components of innate immune system of eukaryotes and are not prone to the conventional mechanisms that are responsible of drug resistance. Fish are an important source of AMPs and, recently, we have isolated and characterized a new 22 amino acid residues peptide, the chionodracine (Cnd), from the Antarctic icefish Chionodraco hamatus . In this paper we focused on a new Cnd-derived mutant peptide, namely Cnd-m3a, designed to improve the selectivity against prokaryotic cells and the antimicrobial activity against human pathogens of the initial Cnd template. Cnd-m3a was used for immunization of rabbits, which gave rise to a polyclonal antibody able to detect the peptide. The interaction kinetic of Cnd-m3a with the Antarctic bacterium Psychrobacter sp. (TAD1) was imaged using a transmission electron microscopy (TEM) immunogold method. Initially the peptide was associated with the plasma membrane, but after 180 min of incubation, it was found in the cytoplasm interacting with a DNA target inside the bacterial cells. Using fluorescent probes we showed that the newly designed mutant can create pores in the outer membrane of the bacteria E. coli and Psychrobacter sp. (TAD1), confirming the results of TEM analysis. Moreover, in vitro assays demonstrated that Cnd-m3a is able to bind lipid vesicles of different compositions with a preference toward negatively charged ones, which mimics the prokaryotic cell. The Cnd-m3a peptide showed quite low hemolytic activity and weak cytotoxic effect against human primary and tumor cell lines, but high antimicrobial activity against selected Gram – human pathogens. These results highlighted the high potential of the Cnd-m3a peptide as a starting point for developing a new human therapeutic agent. Highlights: Fish antimicrobial peptides are relevant as new possible antibiotics. A new fish-derived antimicrobial peptide has been designed. Its interactions with bacterial membranes have been investigated in detail. The peptide shows high antimicrobial activity against known pathogenic Gram – bacteria.